Histological and Morphological Analysis of the Hippocampal Subfields in the Adult Rat - Hussein, Ahmed A.W. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: The hippocampus is empirically assumed to have different functions, of which the best known are: the representation of self-location in cognitive dimensions, and the storage and retrieval of memory. Materials and methods: Eleven adult male albino rats were used. Brain specimens were processed into paraffin blocks, sectioned (10 μm thick), and stained using Haematoxylin and Eosin, and Luxol Fast Blue MBS counterstained with Cresyl Violet. Morphometric analysis was done through eyepiece micrometers. Results: The lamellae of the hippocampus were morphometrically evaluated in context of embryogenesis and nerve fiber content. Conclusion: This study confirmed the existence of differences in nerve fiber distribution among the subfields of the hippocampus which is attributed to differences in the embryonic development processes and to the selectivity of the different connections.